2020
DOI: 10.1111/bcp.14350
|View full text |Cite
|
Sign up to set email alerts
|

Association of different oral anticoagulants use with renal function worsening in patients with atrial fibrillation: A multicentre cohort study

Abstract: To investigate the decline of estimated glomerular filtration rate (eGFR) in patients with atrial fibrillation (AF) treated with vitamin K antagonists (VKAs) or non-VKA oral anticoagulants (NOACs). Methods: Multicentre prospective cohort study including 1667 patients with nonvalvular AF. The eGFR was assessed by the CKD-EPI formula at baseline and during follow-up. The primary endpoint of the study was the median annual decline of eGFR according to VKA (n = 743) or NOAC (n = 924) use. As secondary endpoints, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 23 publications
0
15
0
1
Order By: Relevance
“…There was a small, statistically significant decline in renal function among patients receiving rivaroxaban compared with patients receiving warfarin in the subgroup analysis of ROCKET-AF trial [6,7]. In a recent multicenter prospective cohort study, Pastori et al reported that DOACs provided a slower decline in renal function compared to those using warfarin [9]. Therefore, the results about the decline in renal function after long-term anticoagulants use is still controversial and the underlying mechanism is not clear.…”
Section: Anticoagulants Use and The Decline In Renal Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…There was a small, statistically significant decline in renal function among patients receiving rivaroxaban compared with patients receiving warfarin in the subgroup analysis of ROCKET-AF trial [6,7]. In a recent multicenter prospective cohort study, Pastori et al reported that DOACs provided a slower decline in renal function compared to those using warfarin [9]. Therefore, the results about the decline in renal function after long-term anticoagulants use is still controversial and the underlying mechanism is not clear.…”
Section: Anticoagulants Use and The Decline In Renal Functionmentioning
confidence: 99%
“…On the contrary, in the US medical care database, rivaroxaban was associated with a 19% reduction in the hazard of acute kidney injury (AKI) and an 18% reduction in progression to stage 5 CKD or hemodialysis compared with warfarin in patients with AF [ 8 ]. Moreover, in a recent multicenter prospective cohort study, patients taking direct oral anticoagulants (DOACs) showed a slower decline in renal function compared with those taking warfarin, but the favorable association between DOAC use and decline of renal function was partially lost in patients with diabetes [ 9 ]. Thus, there are different impacts of DOACs and warfarin on renal decline in different population with AF.…”
Section: Introductionmentioning
confidence: 99%
“…Non-vitamin K antagonist oral anticoagulants (NOACs) are recommended in preference to vitamin K antagonists for stroke prevention in high risk AF patients without EHRA type I VHDs [1]. And taking NOACs was conducive to postponing the deterioration of renal function compared to use of warfarin [21]. However, NOACs were not always available due to their high costs and unsupported by local health insurance in China, thus warfarin was still the only recorded oral anticoagulant in our study population.…”
Section: Table 4 Multivariable Cox Regression Analysis Of All-cause Dmentioning
confidence: 98%
“…In contrast, DOACs have consistently demonstrated more preservation, or slower decline in renal function, compared with warfarin. [59][60][61] Dabigatran 75 mg twice daily is recommended for patients with a CrCl 15 to less than 30 mL/min. 14 Although this dose provides similar PK/PD compared with those receiving 150 mg twice daily with normal renal function, data are otherwise limited, and sometimes still suggest worse outcomes compared with warfarin.…”
Section: Advanced Renal Impairment Summarymentioning
confidence: 99%